The Two Hit Hypothesis: An Improved Method for siRNA-Mediated Gene Silencing in Stimulated Primary Human T Cells. - FREELEY, MICHAEL (My University, 2013)
Small interfering RNAs (siRNAs) have revolutionised cellular and molecular biology by uncovering new roles for genes in various biological processes and by providing new opportunities to silence gene expression for therapeutic purposes. A limiting factor of siRNA-mediated gene silencing, however, is the ability to efficiently deliver these molecules into hard-to-transfect cell types such as primary T cells. Nucleofection® technology, marketed by Lonza (Amaxa®), is an electroporation-based method that is commonly used for the delivery of siRNAs and plasmids into primary T cells. In this study we found that the recommended programs for nucleofection of stimulated primary human T cells with siRNAs inhibited cellular proliferation and were associated with a significant loss of cell viability. Furthermore, viable cells that survived the nucleofection procedure were perturbed in their ability to polarise in response to chemokine stimulation in comparison to mock nucleofections. We therefore evaluated other nucleofection programs and highlight one that resulted in significant silencing at the protein level following nucleofection with siRNAs, while maintaining cell viability and responsiveness to chemokine stimulation. Further optimisation of this method revealed that a second nucleofection with siRNAs after 72 h significantly increased silencing compared to a single nucleofection. This new and improved two-hit nucleofection method for siRNA-mediated gene silencing in stimulated primary human T cells will therefore permit the investigation of genes and signalling pathways in the T cell immune response.
PUBLISHED
Keywords: Transfection; Gene silencing; siRNA; Nucleofection; T cell; Immunology, Inflammation & Infection